ANALYSIS OF MICRO NUTRITIONAL CONSUMPTION AND FERRITIN LEVELS OF ADOLESCENT WOMEN IN GIANYAR REGENCY, BALI PROVINCE - Ida Ayu Eka Padmiari; Pande Putu Sri Sugiani (Journal of Social Research, 2022)
Background: Based on Riskesdas, 2018 shows that the prevalence of anemia in women of childbearing age (WUS) in Indonesia is 23.7% with anemia sufferers aged 5-14 years at 26.8%, anemia sufferers aged 15-24 years at 32.0%, anemia aged 25-34 years by 15.1% and anemia patients aged 35-44 years by 16.7%. In Bali, research on the prevalence of anemia in adolescents as far as the author's knowledge is still very minimal. Objective: The purpose of this research in the first year is to determine the relationship between consumption of micronutrients and ferritin levels in adolescent girls in Gianyar Regency, Bali Province. The aim in the second year was to determine the effectiveness of iron folate and Multi Micronutrient Supplements (MMS) in adolescent girls whose hemoglobin or ferritin levels were below normal. This research is an epidemiological study of community nutrition that will be carried out in Gianyar Regency, Bali Province, the first year from March to October 2021 and the second year from March to October 2022. Methods: The first year research method used a community trial with a Cross Sectional design with a sample size of 168 samples. The second year with a different subject design with a sample size of 86 samples consisting of 43 control groups and 43 treatment groups. Results: The results of the study in year 1 (2021) showed that the Ferritin levels of adolescent girls in Gianyar Regency, Bali Province showed 29.2% in the low category (<30 g/l) and 4.8% in the high category (>160 g/l), The average consumption of micronutrients for adolescent girls in Gianyar Regency, Bali Province, namely iron (55%), zinc (74.25%), folic acid (31.7%) and vitamin C (39.2%), there is a relationship Consumption of Micronutrients, namely Folic Acid and Zinc with ferritin levels, while there is no relationship between consumption of iron and Vitamin C with ferritin levels in adolescent girls in Gianyar Regency, Bali Province Conslusion: There is a relationship between consumption of micronutrients, namely Folic Acid and Zinc with ferritin levels, while there is no relationship between consumption of iron and Vitamin C with ferritin levels in young women in Gianyar Regency, Bali Province